2022
DOI: 10.1037/ppm0000295
|View full text |Cite
|
Sign up to set email alerts
|

Dark personality traits and anger in cyber aggression perpetration: Is moral disengagement to blame?

Abstract: A number of dark personality traits (e.g., psychopathy and sadism) have been shown to predict cyber aggression perpetration among emerging adults; however, trait anger and moral disengagement, both useful in understanding other forms of aggression, have not typically been included in these models. The present study tested a model in which dark personality traits and trait anger were expected to predict cyber aggression perpetration and moral disengagement was expected to partially mediate these relationships. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 89 publications
(146 reference statements)
2
18
2
Order By: Relevance
“…Potentially, the predictive value of advantageous comparison outweighed and subsequently reduced the effects of the other two mechanisms in the cognitive restructuring cluster. Third, while previous studies of moral disengagement and cyber aggression have typically viewed moral disengagement as a unitary construct (e.g., Nocera et al, 2020;Runions & Bak, 2015) or four clusters (Falla et al, 2020), our results suggest that it may be beneficial to examine the role of specific moral disengagement mechanisms too. While the moral disengagement mechanisms together predicted cyber aggression perpetration, only dehumanization, advantageous comparison, distortion of consequences, and displacement of responsibility were significant, unique predictors.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Potentially, the predictive value of advantageous comparison outweighed and subsequently reduced the effects of the other two mechanisms in the cognitive restructuring cluster. Third, while previous studies of moral disengagement and cyber aggression have typically viewed moral disengagement as a unitary construct (e.g., Nocera et al, 2020;Runions & Bak, 2015) or four clusters (Falla et al, 2020), our results suggest that it may be beneficial to examine the role of specific moral disengagement mechanisms too. While the moral disengagement mechanisms together predicted cyber aggression perpetration, only dehumanization, advantageous comparison, distortion of consequences, and displacement of responsibility were significant, unique predictors.…”
Section: Discussionmentioning
confidence: 61%
“…Bandura (2002) clustered these mechanisms into four central strategies: cognitive restructuring, minimizing one's agentive role, disregarding/distorting consequences, and blaming/dehumanizing. Although there is ample evidence that overall moral disengagement (i.e., a composite of the eight mechanisms), as well as the four strategy clusters, predict several morally transgressive behaviors, relatively little is known about whether specific mechanisms have distinct correlates (Falla et al, 2020;Marin-Lopez et al, 2020;Nocera et al, 2020;Runions & Bak, 2015). Researchers have highlighted differences between the moral disengagement mechanisms (Falla et al, 2020(Falla et al, , 2021Runions et al, 2019;Thornberg & Jungert, 2014), suggesting that evaluating them individually may provide a more accurate understanding of their role.…”
Section: Moral Disengagement Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other personality traits like anger and spitefulness, have been notated in current literature to be negatively associated with moral behavior. Nocera et al (2021) found a statistically significant relationship between online aggression and trait-anger, which was mediated by moral disengagement. A 2020 study suggests that spitefulness is not related to moral binding values (ingroup loyalty, purity, respect for authority, etc.)…”
Section: Morality and Personalitymentioning
confidence: 84%